Mechanisms at the cellular level during induction of high zone tolerance in vitro. - Diener, E; Feldmann, M (1972)
The in vitro induction of high zone tolerance to polymerized flagellin of S. adelaide in CBA mouse spleen cells consists of two stages: (a) Attachment of tolerance inducing concentrations of antigen to the surface of immunocompetent cells. (b) Inactivation of the immunocompetent cells by the surface-bound antigen. The definition of these two stages is based on the finding that trypsin treatment of spleen cells within 16 hr after tolerance induction in vitro completely reverses the state of unresponsiveness. However, reversibility of the tolerant state could not be observed by trypsinization of cells after 3 days of culture with antigen. Trypsin treatment of spleen cells before exposure to antigen prevented the induction of tolerance in vitro. This suggests that antigen binding was abolished by removal of recognition sites by the proteolytic enzyme. © 1972.